Result Analysis of Students Using Fuzzy Matrices (International Journal of Advanced Research in Science, Management and Technology, 2015)
The Analysis of Result System for an Organization” is an application software to  be  developed  for  the colleges  to  analyze  the result of various exams to  be  conducted  by the  N.M.U. The  college  has  to  analyze  these  results in various  angles to evaluate  the  performance  of  students, calculate  the number of students  eligible to admit to the next year, topper of the every year and  many more.Fuzzy set hypothesis was proposed by Lotfi A. Zadeh also, has been discovered broad applications in different fields. The idea of instability was talked about by utilizing fluffy grids. All through this article [0, 1] indicates the unit interim, as a fluffy Interval. Additionally all fluffy grids are networks however every grid is not fluffy as a rule. We examinations the consequences of three understudies utilizing Fuzzy Matrix Solution (FMS) with the assistance of result of fluffy networks. Under normal network increase this is not a fluffy network, with the goal that we have to characterize good operation analogs to item that the item again happens to be a fluffy network by presenting max-min operation and min-max operation. At long last we finish up the aftereffects of three understudies as pass or come up short utilizing fluffy lattice.
Keywords: FMS, visual basic, indication relation, max-min operation